Zircon‐bearing, crystallized melt inclusions in peritectic garnet from the western Adirondack Mountains, New York State, USA. Issue 4 (9th July 2013) - Darling, R. S.
Abstract: Crystallized melt inclusions (MI) occur in garnet from metapelitic gneiss extracted from a hydroelectric plant on the Black River at Port Leyden, NY (western Adirondack Highlands). The garnet host grains are small (0.5–1.0 mm), euhedral neoblasts that formed peritectically during biotite melting accompanying the Ottawan phase of the Grenville Orogeny. The crystallized MI are typically 10–25 μm in diameter and occur randomly in garnet. Nearly all of the crystallized MI observed contain a relatively large (3–15 μm), often euhedral, zircon grain surrounded by finer‐grained (some <1 μm) phases with energy dispersive X‐ray spectra consistent with biotite, K‐feldspar, quartz, and albite. The inclusions are similar in size and composition to those described in garnet from other migmatites and are similarly interpreted as crystallized anatectic melt. Low Zr solubility in silicate melt indicates that the large zircon grain in each inclusion must be a trapped solid. It is inferred that micrometer‐scale droplets of anatectic melt chemically adhered to occluded zircon grains in biotite while peritectic garnet grew around them. Abstract : Zircon‐bearing, crystallized melt inclusions (MI) occur in peritectic garnet from granulite‐facies, metapelitic gneiss from the western Adirondack Highlands of New York State. The crystallized MI contain micrometer‐ to nanometer‐scale grains of quartz, K‐feldspar, biotite ± albite and a larger grain of zircon. Low Zr solubility in silicate melt indicates the large zircon grain must be a trapped solid. It is inferred that droplets of anatectic melt chemically adhered to occluded zircon grains in biotite while peritectic garnet grew around them.